(untitled) (Marketing Journal, 2025)
The article explores the transformational processes driven by the digital revolution and their impact on the development of small businesses. Particular attention is paid to the new quality of marketing opportunities arising from the use of digital technol ogies such as Big Data, social media, online analytics, and artificial intelligence. It is demonstrated that digitalization enables small enterprises not only to optimize business processes but also to enhance customer engagement, create personalized offer s, and strengthen competitive positions in the market. The study substantiates the need for integrating digital marketing tools into the strategic management of small enterprises.